If it's not what You are looking for type in the equation solver your own equation and let us solve it.
147=3(1+6x)
We move all terms to the left:
147-(3(1+6x))=0
We add all the numbers together, and all the variables
-(3(6x+1))+147=0
We calculate terms in parentheses: -(3(6x+1)), so:We get rid of parentheses
3(6x+1)
We multiply parentheses
18x+3
Back to the equation:
-(18x+3)
-18x-3+147=0
We add all the numbers together, and all the variables
-18x+144=0
We move all terms containing x to the left, all other terms to the right
-18x=-144
x=-144/-18
x=+8
| (16x)^2+(12x)^2=x^2 | | y=-143.3(4)^2+1823.3(4)+6820 | | 4+3(2x-4)=28 | | 50x-1100=-15x+2150 | | h=-16(4)^2+129(4) | | 2.2z-4.4=1.8z | | 5^2-3x=625 | | -t/10+7/10=2t/5+t/2+1 | | (2D3-D2+36D-18)y=0 | | 1/2(x-4))=3/4(2x-7) | | 3(4x+5)-6(3x-2)=5x+7 | | (5-7x)/(2+4x)=-19 | | 3y-2/3+(2y+3)/3=(y+7)/6 | | y+12y+36y=0 | | y(0)=1 | | 176=(x+2)(2x+10) | | -2(x-3)+5=4-7(2x-1) | | X/3-(x-2)/2=7/3x | | 5×+8=2x-10 | | E^(2x+3)=37 | | 6n-5=-8n+13 | | -47y=-141 | | 6n-5=8n+13 | | (3x-10)-2x=15 | | 4x÷7=23 | | (4+g)(-11=121 | | 14-7x/10=8 | | (x-10)^2=784 | | 2-x+5/3=2x-4/4-x | | 2x^2-5x+8=23 | | -3y-(7)=2 | | 5x(3x-1)=120 |